PERAN FINANCIAL ACTION TASK FORCE (FATF) DALAM HARMONISASI PENANGGULANGAN PENCUCIAN UANG GLOBAL - Nurhani Mouriska; Ani Purwati (PT. Hasba Edukasi Mandiri, 2025)
This study examines the role of the Financial Action Task Force (FATF) in combating organized financial crimes, particularly through the harmonization of international regulations against money laundering. As an intergovernmental body, FATF has established 40 Recommendations that serve as global standards for the prevention and suppression of money laundering and terrorist financing. This research employs a normative juridical method with statutory, historical, and comparative approaches, utilizing primary legal materials such as national legislation and official FATF documents, secondary legal materials from academic literature and legal journals, and tertiary materials such as legal dictionaries. The findings reveal that the harmonization of international regulations through FATF has driven significant policy reforms in Indonesia, including the strengthening of beneficial ownership regulations, the expansion of supervision over non-financial sectors, and the enhancement of cross-border cooperation in financial intelligence exchange. Nevertheless, challenges remain in implementation, particularly due to limited law enforcement capacity, inconsistent understanding among business actors, and regulatory gaps in the digital sector. This study recommends strengthening inter-agency coordination, adopting international best practices such as a public beneficial ownership registry, and establishing a specialized financial investigation unit with cross-border forensic expertise. The findings contribute to the literature on international law and public policy by highlighting the importance of adaptive global regulatory harmonization in addressing evolving financial crime schemes.